Long-Term Outcome After Out-of-Hospital Cardiac Arrest: An Utstein-Based Analysis - Baldi, Enrico; Compagnoni, Sara; Buratti, Stefano; Primi, Roberto; Bendotti, Sara; Currao, Alessia; Gentile, Francesca Romana; Sechi, Giuseppe Maria; Mare, Claudio; Bertona, Roberta; Raimondi Cominesi, Irene; Taravelli, Erika; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: No data are available regarding long-term survival of out-of-hospital cardiac arrest (OHCA) patients based on different Utstein subgroups, which are expected to awfully differ in terms of survival. We aimed to provide the first long-term survival analysis of OHCA patients divided according the Utstein categories. Methods: We analysed all the 4924 OHCAs prospectively enrolled in the LombardiaCARe from 2015 to 2019. Pre-hospital data, survival and cerebral performance category score (CPC) at 1, 6 and 12 months and then every year up to 5 years after the event were analysed for each patient. Results: A decrease in survival was observed during the follow-up in all the Utstein categories. The risk of death of the “All-EMS treated” group exceeded the general population for all the years of follow-up with standardized mortality ratios (SMRs) of 23 (95%CI,16.8-30.2), 6.8 (95%CI,3.8-10.7), 3.8 (95%CI,1.7-6.7), 4.05 (95%CI,1.9-6.9) and 2.6 (95%CI,1.03-4.8) from the first to the fifth year of follow-up. The risk of death was higher also for the Utstein categories “Shockable bystander witnessed” and “Shockable bystander CPR”: SMRs of 19.4 (95%CI,11.3-29.8) and 19.4 (95%CI,10.8-30.6) for the first year and of 6.8 (95%CI,6.6-13) and 8.1 (95%CI,3.1-15.3) for the second one, respectively. Similar results were observed considering the patients discharged with a CPC 1-2. Conclusions: the mortality of OHCA patients discharged alive from the hospital is higher than the Italian standard population, also considering those with the most favourable OHCA characteristics and those discharged with good neurological outcome. Long-term follow-up should be included in the next Utstein-style revision.